Ulcerative colitis developing after amoebic dysentery in a haemophiliac patient with AIDS. Issue 3 (March 1992) - Sturgess, I; Greenfield, S M; Teare, J; O'Doherty, M J
Abstract : Severe diarrhoea in patients with the acquired immune deficiency syndrome (AIDS) is usually a manifestation of gastrointestinal infection by a variety of organisms. We report a patient with low CD4 T cell counts who developed ulcerative colitis after amoebic dysentery. He subsequently developed acute ulcerative colitis with toxic dilatation while he was severely immunocompromised. He responded to corticosteroids and mesalazine and remains well on maintenance therapy.